Efficacy of Homeopathy in Addition to a Multidisciplinary Intervention for Overweight or Obesity in Mexican Adolescents: Study Protocol for a Randomized, Double-Blind, Placebo-Controlled Trial - Macías-Cortés, Emma; Arellano-Álvarez, Saraí; Vega-Monroy, Sandra; Vera-Pérez, Violeta; Llanes-González, Lidia; Sánchez-Navarrete, Pilar; Enciso-González, Dolores (Homeopathy, 2020)
Background Current recommendations for treating obesity in adolescence include a comprehensive approach (nutritional, behavioral, and exercise). Calcarea carbonica ostrearum (CCO) is a homeopathic medicine usually prescribed in obese individuals, but its effects on weight and body fat are not completely known.Objective The aim of this study will be to evaluate the efficacy of homeopathic CCO, in addition to a multidisciplinary intervention (diet, motivational support, and exercise program), on body fat and weight in obese adolescents.Methods/Design A randomized, placebo-controlled, double-blind, parallel-group, superiority trial with 3-month study duration will be undertaken. The study will be conducted in a public research hospital in Mexico City, Hospital Juárez de México, in the outpatient services of homeopathy and sports medicine. Eighty non-diabetic adolescents, 12 to 19 years old, who are overweight or obese, will be included. The primary outcome: change in body fat percentage at week 12. The secondary outcomes: change in mean total weight, total body mass index, fat mass index, waist–hip ratio, lean muscle mass, fasting glucose, insulin, insulin resistance, lipid profile, score of Center for Epidemiologic Studies Depression Scale Revised (CESD-R) and score of Screen for Child Anxiety-Related Emotional Disorders (SCARED) at week 12. Efficacy data will be analyzed in the intention-to-treat sample. To determine the difference in the outcomes between groups at baseline and week 12, data will be analyzed using Student's t-test.Discussion This is the first randomized controlled trial aimed to determine the fat-reducing efficacy in obese adolescents of a homeopathic medicine, CCO, given in addition to a multidisciplinary intervention, compared with placebo plus the same intervention. It is an attempt to support scientific evidence in homeopathy for one of the most common chronic diseases, which causes high mortality due to its complications.ClinicalTrials.gov Identifier: NCT03945396 https://clinicaltrials.gov/ct2/show/NCT03945396?term=homeopathy+for+obesity+in+Mexican+adolescents&rank=1
Keywords: overweight; obesity; adolescents; homeopathy; Calcarea carbonica ostrearum